Sejarah Dan Dampak Perang Tabuk: Analisis Mendalam Terhadap Konflik Perbatasan Dalam Perspektif Sejarah Dan Kemanusiaan - Muhammad Basri; Luthfia Rizka Fadhila; Sarah Rizky Aulia; Septia Putri Anggraini (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The purpose of this research is to find out the History and Impact of the Tabuk War: An In-depth Analysis of the Border Conflict in Historical and Humanitarian Perspective. The Battle of Tabuk marked a monumental event in Islamic history in 630 AD. The research approach in this Literature Review study is one type of qualitative research method in which research is conducted in libraries through the collection of books, documents, archives, and other types. This war had a significant impact in Islamic history, both in terms of politics and military. The impacts include strengthening the position of Islam in Arabia, increasing the autonomy of Arab tribes, and asserting Islamic rule over the surrounding territories. In humanitarian terms, the war also demonstrated the importance of diplomacy in resolving conflicts, and provided lessons on the importance of peace and justice in relations between nations.